Outcome Report. Agroecological Transitions: Inclusive Digital Tools (ATDT) - Funk, Evelyn; Rassmann, Kornelia; Sette-Mosaner, Marcelo; Van Tuan, Vu (International Center for Tropical Agriculture, 2025)
The Agroecological Transitions: Digital Tools (ATDT) project (2022– 2024), led by the Alliance of Bioversity International and CIAT, aimed to promote inclusive digital innovation to support farmers and technical advisors in adopting climate-resilient agroecological practices at scale. The project targeted sustainable rice production in Vietnam and sustainable beef production in Brazil, while providing global guidance and lessons learned for broader application. This section presents ten key messages derived from the Outcome Harvesting evaluation of the ATDT project, offering a summary of its core findings, critical achievements, challenges, and lessons learned. These concise and accessible takeaways distill the essence of the study, highlighting the project’s success in advancing inclusive digital innovation. This format serves as an alternative to the traditional executive summary, enhancing the practical value of the evaluation report for a diverse range of users.